Revolution from Below in Panguipulli: Agrarian Reform and Political Conflict Under the Popular Unity in Chile - Robles-Ortiz, C (Blackwell Publishing Ltd, 2018)
This article examines the political conflict in rural society during the Popular Unity Government (1970–73) by focusing on the mobilization of forestry workers in Panguipulli, a district in southern Chile. Adopting land invasions as their main strategy in the struggle for land and power, Panguipulli workers experienced a radical politicization by aligning themselves with the Peasant Revolutionary Movement, the “peasant front” of the Revolutionary Left Movement. Because of its relation with this emerging “new left,” rural mobilization was a significant expression of the “revolution from below”, which challenged the Popular Unity s “Chilean road to socialism.” Moreover, because rural mobilization also took place in other areas throughout Chile where the Revolutionary Left Movement was influential, it gave rise to a grassroots project for radicalizing the government s agrarian reform. As a result, the rural “revolution from below” strongly influenced the content and trajectory of political conflict under the Popular Unity Government. © 2018 John Wiley & Sons Ltd